2017
DOI: 10.1080/13543784.2017.1386172
|View full text |Cite
|
Sign up to set email alerts
|

Targeting triple negative breast cancer with histone deacetylase inhibitors

Abstract: Triple negative breast cancer (TNBC) is a heterogeneous disease characterized by poor outcomes, higher rates of relapse, lack of biomarkers for rational use of targeted treatments and insensitivity to current available treatments. Histone deacetylase inhibitors (HDACis) perform multiple cytotoxic actions and are emerging as promising multifunctional agents in TNBC. Areas covered: This review focuses on the challenges so far addressed in the targeted treatment of TNBC and explores the various mechanisms by whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 69 publications
3
46
1
Order By: Relevance
“…We have previously shown that aggressive breast cancer subtypes, such as TNBCs [34–36], specifically claudin-low TNBCs [36], are susceptible to DACi. Treatment with romidepsin and panobinostat reversed the mesenchymal phenotype of TNBCs, in addition to suppressing tumorigenesis and metastasis [35], consistent with findings from other groups [33, 37]. Maintenance of a mesenchymal phenotype is important in TNBC biology; the process through which cells acquire these cellular characteristics, also known as the epithelial-to-mesenchymal transition (EMT), is one proposed mechanism that is integral in the initiation of metastasis.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…We have previously shown that aggressive breast cancer subtypes, such as TNBCs [34–36], specifically claudin-low TNBCs [36], are susceptible to DACi. Treatment with romidepsin and panobinostat reversed the mesenchymal phenotype of TNBCs, in addition to suppressing tumorigenesis and metastasis [35], consistent with findings from other groups [33, 37]. Maintenance of a mesenchymal phenotype is important in TNBC biology; the process through which cells acquire these cellular characteristics, also known as the epithelial-to-mesenchymal transition (EMT), is one proposed mechanism that is integral in the initiation of metastasis.…”
Section: Introductionsupporting
confidence: 74%
“…DACi have emerged as an effective targeted therapy in breast carcinomas in preclinical studies [32], specifically in TNBC subtypes [33]. Our laboratory has extensively evaluated DACi in TNBC cells and tumors [34–36]; we observed different biologic effects on tumorigenesis and metastasis with pan-DAC inhibition compared to class-specific inhibitors [35].…”
Section: Introductionmentioning
confidence: 99%
“…Crucial preclinical trials on HDAC inhibitors (panobinostat, vorinostat, and entinostat) exert an anti-proliferative effect on TNBC cells and control tumor growth by multiple mechanisms of action, including apoptosis and regulation of the epithelial to mesenchymal transition (EMT). HDAC inhibitors such as suberoylanilidehydroxamic acid (SAHA), sodium butyrate, mocetinostat, panobinostat, entinostat, YCW1 and N-(2-hydroxyphenyl)-2-propylpentanamide have shown promising therapeutic outcomes against TNBC, especially when they are used in combination with other anticancer agents [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Histone deacetylase (HDAC) inhibitors were reported to show promising activity in triple‐negative breast cancer . Indeed, linking of tamoxifen to the histone deacetylase inhibitor vorinostat resulted in a conjugate with higher cytotoxicity in MCF‐7 and MDA‐MB‐231 cells than the parent drugs .…”
Section: Pharmacology Of Drug‐drug Conjugatesmentioning
confidence: 99%
“…Histone deacetylase (HDAC) inhibitors were reported to show promising activity in triple-negative breast cancer. 34 Indeed, linking of tamoxifen to the histone deacetylase inhibitor vorinostat resulted in a conjugate with higher cytotoxicity in MCF-7 and MDA-MB-231 cells than the parent drugs. 40 The RU39411-like antiestrogen compound conjugated with doxorubicin exhibited lower IC 50 values (ie, greater potency) compared to doxorubicin only or doxorubicin plus the linker when tested in MCF-7 cells, but not MDA-MB-231 cells.…”
Section: Linker Designmentioning
confidence: 99%